Comparing Public Space for Women in Mlangi, Yogyakarta and Cumalikizik, Bursa - Murti, Desy Ayu Krisna; Akyol, Ozlem (Journal of Asian Wisdom and Islamic Behavior, 2024)
Public space is an extremely vital necessity in social life. In architecture, public space belongs to everyone living in an area, city, or settlement. Public spaces like communal spaces have particular profiles. If we talk about the need for gender determination, we can say more about women’s space. Yogyakarta and Bursa are similar cities characterized with a majority of Muslim citizens. Both have Muslim Settlements known, respectively, as Pathok Negoro and the area of Cumalikizik. Pathok Negoro, specifically located in Mlangi, has two patterns to encircling the number of nodes for the public spaces in the form of prayer room/mushola and pondok pesantren (Islamic boarding school) as the new nuclei at the neighborhood level. These spaces are special for women and an imam who leads in each Mushola or prayer room. The existence of two neighborhood levels in Mlangi is based on religious activities, namely of the santri (Islamic boarding school students) and Mlangi citizens. Mlangi accommodates several pondok pesantren so there is ample space to expand (multi nuclei/polycentric). Around the Cumalikizik area, there is a camii or Mosque and it serves as the most central communal space for women.